2010
DOI: 10.1007/s00417-010-1395-9
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctivocystorhinostomy with Jones tube—is it the surgery for children?

Abstract: CDCR appears to be a reasonable procedure in children over 10 years old. Experience in lacrimal surgery (pediatric dacryocystorhinostomy, CDCR in adults), and good cooperation and compliance of children are a fundamental assumption for successful pediatric CDCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…However, this procedure is rarely performed in children because of the difficulties encountered. 7 Good patient cooperation and compliance with the Jones tube are absolutely essential for surgical success. Complication rates of conjunctival dacryocystorhinostomy in children are significantly higher than in adults, with tube malposition and extrusion seen commonly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this procedure is rarely performed in children because of the difficulties encountered. 7 Good patient cooperation and compliance with the Jones tube are absolutely essential for surgical success. Complication rates of conjunctival dacryocystorhinostomy in children are significantly higher than in adults, with tube malposition and extrusion seen commonly.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates of conjunctival dacryocystorhinostomy in children are significantly higher than in adults, with tube malposition and extrusion seen commonly. 7 Because of the success noted in adults who received botulinum toxin injections in the lacrimal gland for treatment of epiphora, this method of treatment was offered to children with proximal lacrimal drainage obstruction. The results reported herein demonstrate similar results in children as in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The mean follow-up was specified in 41 studies. 2,[10][11][12][13][14][17][18][19][20][21]23,[25][26][27][28][29][30][32][33][34][38][39][40][41][42][43][44][45][46][47][48][49]51,54,[57][58][59][60][61] Mean follow-up of all included patients was 24 ± 17.6 months. In 12 studies only range or median of follow-up duration was reported.…”
Section: Follow-upmentioning
confidence: 99%
“…The etiology of canalicular obstruction was reported in 44 studies, 2,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][30][31][32][33][34][35][36]38,39,[41][42][43][45][46][47][48][49][50][51][53][54][55]57,58 in which a total of 1845 patients were included. The distribution of patients according to etiology was as follows: trauma (25.5%); congenital (16.7%); cancer-related (secondary to surgery); radiation or chemotherapy (7.5%); idiopathic (6.5%); and defined as failed DCR (9.1%).…”
Section: Etiology Of Canalicular Obstructionmentioning
confidence: 99%
See 1 more Smart Citation